Matrine@chitosan-D-proline nanocapsules as antifouling agents with antibacterial properties and biofilm dispersibility in the marine environment - Hao, Xiangping; Yan, Weilu; Yang, Jingzhi; Bai, Yun; Qian, Hongchang; Lou, Yuntian; Ju, Pengfei; Zhang, Dawei (Frontiers in Microbiology, 2022)
Antifoulants are the most vital substances in antifouling coatings to prevent marine organisms from colonizing the undersea substrate surfaces. In addition to antibacterial performance, inhibition of biofilm formation is an important criterion for antifouling coatings. In this study, we synthesized pH-responsive matrine@chitosan-D-proline (Mat@CS-Pro) nanocapsules of about 280 nm with antibacterial properties and biofilm dispersibility. The prepared Mat@CS-Pro nanocapsules exhibited high-level antibacterial properties, reaching about 93, 88, and 96% for E. coli, S. aureus, and P. aeruginosa, respectively. Such nanocapsules can cause irreversible damage to bacteria and cause them to lose their intact cell structures. Moreover, Mat@CS-Pro nanocapsules also possessed outstanding dispersal biofilm performances, in which the biofilm thickness of E. coli, S. aureus, and P. aeruginosa was decreased by 33, 74, and 42%, respectively, after 3 days of incubation. Besides, the Mat@CS-Pro nanocapsules had remarkable pH-responsive properties. As the environmental pH became acidic, the nanocapsules swelled to about 475 nm and the released concentration could reach 28.5 ppm after immersion for 10 h but maintained a low releasing rate in pH 8 conditions.